IMPLEMENTASI PROGRAM PENANGGULANGAN KEMISKINAN PERKOTAAN (P2KP) DI KECAMATAN TONJONG KABUPATEN BREBES TAHUN 2007 - Rahman, Yozi Aulia (JEJAK: Jurnal Ekonomi dan Kebijakan, 2010)
Poverty is a serious problem, it’s happened in all the world, such as Indonesia. In September 2006, BPS announced that the poverty rate in Indonesiahad increased during the period February 2005 to march 2006 from 16.0 percent to 17.75 percent contrast to steady declines in the poverty rate since the crisis. Number of Poverty in Indonesiain 2006 have been reached 35,5 milion people. Government of Indonesiahas implemented programs to reduce poverty until village level. These programs such as IDT, PPK, BLT, etc. But, that programs just a short run programs, not long run programs. As long run program, P2KP has many programs, such as micro credits, infrastructure, and training. In Pepedan and Linggapura village implemented infrastructure programs. Its first priority programs because there many roads in that village are broken and disturbs local economic activities. BKM and KSM managed this program so that is success. Based on SWOT analysis, appropriate strategy to improve the function of P2KP is by intregrated horizontal strategy. It means, Local Government (Brebes Regency Goverment) must have policy strategic and must cooperation with BKM, KSM and people in village. Project evaluate (Inputs, Outputs, Outcames, Benefits, Impact) needs to know programs running.